Sustainability of ijtihad and fatwa to respond the issue of indirect contributions in matrimonial property claim: A critical assessment fiqh of property - Yusoff, Mus’ab; Urus, Nur Sarah Tajul; Yusoff, Umair; Thahir, Mohamad Fauzi Md; Othman, Siti Nurul Husna; Zainon, Masyitah Mohd; Samsudin, Mohd Syahmil bin (Linguistics and Culture Review, 2021)
The issue of sustainability of ijtihad and fatwas to elaborate on polemics of indirect contributions in matrimonial property claims has become an important issue today. The selection of the right ijtihad and fatwa will ensure that critical discussions in this matter can be photographed to a knowledgeable society. Many findings of jurisprudence writing stated the main methods in ijtihad and fatwas used by fuqahak of the past and contemporary to draw interesting discussions on this issue, but in the context of indirect contributions in matrimonial property claims, there is still much to be clarified. The main objective of this study is to find out the method of ijtihad and fatwa in the book of fiqh applied by the jurists in this issue. This study is qualitative in which a total of 20 books of turath have been researched and understood descriptively. The main collection methods used were in-depth reading and analysis and narrative evaluation was used to analyze the findings obtained. The results of the analysis prove that the indirect contribution related to housework and outdoor work, can be done Akad al-Ijarah for the wife is eligible to take a certain wage according to the jumhur view.